Drosophila: A Model for Understanding Obesity and Diabetic Complications - Teleman, A. A.; Ratzenböck, I.; Oldham, S. (Experimental and Clinical Endocrinology & Diabetes, 2012)
The molecular mechanisms underlying development of obesity and diabetic complications are not well understood. Drosophila has become a popular model organism for studying a variety of human diseases. We discuss here emerging Drosophila models of obesity and diabetic complications.
Keywords: neuropathy; obesity; signal transduction